Eight Grade Students Difficulties in Translating Narrative Text - Nopa Yusnilita (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2018)
The objective of this research was conducted to find out the students’ difficulties in translating narrative text to the eight grade students of SMP 7 OKU and to find out the factors that influence students’ difficulties in translating narrative text to the eight grade students of SMP 7 OKU. To analyzed the data the researcher used test and questionnaire as an instrument. The methodology of this research was descriptive method. From the population, the researcher took all of ninth students as a sample, and the total number of population were 70 Students. The samples were taken by using purposive sampling. The students’ mean scores 55.31 it meant that the eight grade students’ difficulties at SMP 7 OKU was poor level in translating narrative text. The three aspects of the scoring translation scale, the researcher found that high difficulties were idea development ability with the total percentage was 42.09%. Based on the result of the questionnaire the researcher found the main factor that influence the students’ difficulties in translating narrative text were teaching by using media the total of percentage score was 25.65%. Key words: Difficulties, Translating, Narrative Text